De validiteit van het beoordelen van docentcognities en docentgedrag in docentportfoliobeoordelingen - Schaaf der van , M.; Stokking, K.; Verloop, N. (Pedagogische Studiën, 2008)
This study focuses on the relation between teacher beliefs and teacher behaviour in teacher portfolio assessment. Eighteen experienced teachers developed portfolios about their cognitions and behaviour in instructing, coaching and assessing students’ research skills in Social Sciences. We qualitatively analysed the beliefs and behaviour of 18 teachers as described in their portfolios. In addition, each portfolio was independently assessed by two trained raters on eight content standards (assessment criteria) and the teachers’ classroom behaviour was assessed by their own students in a questionnaire (n = 317). Linear multilevel analysis showed that the students’ assessments of their teachers’ behaviour could be significantly predicted by the raters’ assessments of the teachers’ beliefs and behaviour as described in their portfolios. Teachers with high raters’ assessments on the content standard THINK (the deliberate choice of teaching strategies that meet students’ abilities) had significantly higher student assessments than teachers who were judged low on this content standard. Implications of the results are discussed and suggestions for further research are given.